Generalized nonlinear implicit quasivariational inclusions. Issue 3 (11th July 2005) - Fang, Ya-Ping; Huang, Nan-Jing; Kang, Jung Im; Cho, Yeol Je
Abstract : We introduce and study a new class of generalized nonlinear implicit quasivariational inclusions involving relaxed Lipschitzian mappings. We prove the existence of solution for the generalized nonlinear implicit quasivariational inclusions and construct some new stable perturbed iterative algorithms with errors. We also give an application to a class of generalized nonlinear implicit variational inequalities.